2013
DOI: 10.3991/ijim.v7i3.2888
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Technology for Fostering Intellectual Engagement

Abstract: Student engagement, and in particular intellectual engagement, has been identified as a key factor in learning at the high school level. While this type of engagement has an impact on student learning in fields related to science, technology, engineering and mathematics (STEM), it also has a positive impact on the learning of other disciplines such as English, Fine Arts, and Social Sciences. This report describes a set of projects co-designed by teachers and education specialists aimed at engaging students int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The positive educator perceptions concerning textbook utilization in nurturing spatial thinking underscore the indispensable role of technology as a pedagogical adjunct. The current educational milieu witnesses educators recognizing the imperativeness of meticulously curating learning experiences to intellectually engage learners [52]. The supportive features embedded within the STEM-integrated mobile digital textbook-memo pads, highlighting utilities, integrated QR code scanners, navigational aids, GeoExplore, and GeoInfo visualization options-act as catalysts in refining spatial cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The positive educator perceptions concerning textbook utilization in nurturing spatial thinking underscore the indispensable role of technology as a pedagogical adjunct. The current educational milieu witnesses educators recognizing the imperativeness of meticulously curating learning experiences to intellectually engage learners [52]. The supportive features embedded within the STEM-integrated mobile digital textbook-memo pads, highlighting utilities, integrated QR code scanners, navigational aids, GeoExplore, and GeoInfo visualization options-act as catalysts in refining spatial cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Delialioglu, O., et al [15] demonstrated that real interactive learning activities, team cooperation, and personalized learning of students play important roles in blended learning courses. Preciado-Babb, A. P., et al [16] believed that students' use of mobile technologies could significantly improve their learning engagement. Schols, M. [17] found four factors that encourage teachers and educators to participate in technological learning.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The data for the overall three-year design-based research is extensive and include both quantitative and qualitative sources-see [18] for more information. The data for the case reported in this paper comprises: class observations, interviews with teachers and students, documents used for the project, and filed notes taken by one research member who attended the sessions of the project.…”
Section: The Design-based Researchmentioning
confidence: 99%
“…We have been particularly interested in promoting intellectual engagement, as described in [17] and [18]. The focus on student engagement springs from an interests on students' life well beyond academic performance at school.…”
Section: A Focus On Intellectual Engagementmentioning
confidence: 99%
See 1 more Smart Citation